KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA DAN IKLIM SEKOLAH YANG POSITIF DI LEMBAGA PENDIDIKAN - Lutfiya, Amaliyah Khoirun Nisa; Efendi, Nur (Department of Islamic Education Management, 2025)
The implementation of a good and appropriate school culture will have a significant impact on student learning activities and can also motivate teachers to work more effectively and efficiently to achieve good teacher performance. This research uses a literature-based approach, utilizing data derived from scientific publications, articles, and previous research, such as relevant theses. The purpose of this study is to provide a comprehensive overview and analysis of the relationship between school culture and school climate. The research aims to explore indicators and techniques to foster a positive culture in schools, as well as the role of leadership in improving educational outcomes through culture-building efforts. The research findings show that school culture refers to the overall quality of school life, which develops and grows through the embodiment of certain values and collective spirit within the school. An optimal school climate and culture is defined as the establishment of a safe, pleasant and well-organized learning environment to facilitate effective learning. Markers of a positive school culture and climate include a strong sense of loyalty, the establishment of a safe and pleasant school environment, and the cultivation of a deep sense of belonging among all members of the school community. In addition, when a school develops an appropriate culture and atmosphere, students will feel at ease, feel safe and exhibit a favorable attitude towards their educational institution.